Fun Education: Penerapan Pembelajaran Edutainment dalam Pembelajaran Anak Usia Dini - Hayati, Firdha; Safitri, Hana Ika; Fitria, Fadilatul; Fashlah, Anggita Gunati (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2024)
Teachers' readiness to educate in terms of the teaching and learning process, learning methods, learning media, strategies, and learning conditions must be maximized. Varied learning methods can prevent the learning process in the classroom from being ineffective. One learning approach that can be used to make the learning process effective is edutainment. Edutainment not only makes the learning process more enjoyable but also increases the effectiveness and quality of education in a way that is adaptive and oriented to the needs of the digital generation. This study is based on how edutainment education is applied to Play Group (KB) Mutiara Ummi Kalasan. The purpose of this study was to describe the concepts and methods of edutainment applied at Play Group (KB) Mutiara Ummi Kalasan. This study uses descriptive qualitative research with data analysis techniques, such as data reduction, data presentation (data display), drawing conclusions, and verification. In this study, researchers found there were five concepts of edutainment learning, namely: a) risk-free learning environment, b) triune brain theory, c) active learning, d) Learning styles, and e) SAVI learning when the research shop place and four methods used namely a) playing method, b) storytelling method, c) singing method, and d) question and answer method.